The East and West Indian mirror : being an account of Joris van Speilbergen's voyage round the world (1614-1617), and the Australian navigations of Jacob le Maire /: being an account of Joris van Speilbergen's voyage round the world (1614-1617), and the Australian navigations of Jacob le Maire. (2017) - Unknown
No abstract available